Enhancing linkages between healthy diets, local agriculture, and sustainable food systems: The school meals planner package in Ghana - Fernandes, Meenakshi; Galloway, Rae; Gelli, Aulo; Mumuni, Daniel; Hamdani, Salha; Kiamba, Josephine; Quarshie, Kate; Bhatia, Rita; Aurino, Elisabetta; Peel, Francis; Drake, Lesley (SAGE Publications, 2016)
Interventions that enhance linkages between healthy diets and local agriculture can promote sustainable food systems. Home-grown school feeding programs present a promising entry point for such interventions, through the delivery of nutritious menus and meals.To describe the adaptation of the School Meals Planner Package to the programmatic and environmental reality in Ghana during the 2014 to 2015 school year.Guided by a conceptual framework highlighting key considerations and trade-offs in menu design, an open-source software was developed that could be easily understood by program implementers. Readily available containers from markets were calibrated into “handy measures” to support the provision of adequate quantities of food indicated by menus. Schools and communities were sensitized to the benefits of locally sourced, nutrient-rich diets. A behavior change communication campaign including posters and songs promoting healthy diets was designed and disseminated in schools and communities.The School Meals Planner Package was introduced in 42 districts in Ghana, reaching more than 320 000 children. Monitoring reports and feedback on its use were positive, demonstrating how the tool can be used by planners and implementers alike to deliver nutritious, locally-sourced meals to schoolchildren. The value of the tool has been recognized at the highest levels by Ghana’s government who have adopted it as official policy.The School Meals Planner Package supported the design of nutritious, locally sourced menus for the school feeding program in Ghana. The tool can be similarly adapted for other countries to meet context-specific needs.